2018
DOI: 10.17951/pjss.2017.50.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of low-molecular-weight organic acids and creosote on phosphatase activities in sandy soil

Abstract: Abstract. This paper assesses the impact of creosote and low-molecular-weight organic acids (LMWOAs) on the activity of acid phosphomonoesterase, alkaline phosphomonoesterase, phosphotriesterase, and inorganic pyrophosphatase in soil. The experiment was carried out on loamy sand samples with organic carbon content of 8.71 g·kg -1 , with the following variable factors: dosages of creosote: 0, 0.5%, and 2.5%; type of LMWOAs: oxalic acid, tartaric acid, and citric acid in the amount of 50 mmol·kg -1 of soil; days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…After the application of citric acid at a dose of 100 mg·kg 1 DM, an increase in RS value to 0.076 was observed on day 14 and at the dose of 150 mg·kg 1 DM on days 14 and 28 (by 0.136 and 0.072, respectively). Our previous study on the influence of low-molecular-weight organic acids (oxalic acid, tartaric acid, and citric acid) on the phosphatase activity in soil contaminated with creosote showed the highest efficiency of citric acid [ 19 ]. In addition, Huang et al [ 43 ] demonstrated that the presence of low-molecular-weight organic acids in soil influences its sorption of ACP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the application of citric acid at a dose of 100 mg·kg 1 DM, an increase in RS value to 0.076 was observed on day 14 and at the dose of 150 mg·kg 1 DM on days 14 and 28 (by 0.136 and 0.072, respectively). Our previous study on the influence of low-molecular-weight organic acids (oxalic acid, tartaric acid, and citric acid) on the phosphatase activity in soil contaminated with creosote showed the highest efficiency of citric acid [ 19 ]. In addition, Huang et al [ 43 ] demonstrated that the presence of low-molecular-weight organic acids in soil influences its sorption of ACP.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage contribution of this factor in the formation of activity of dehydrogenases and phosphatases in soil contaminated with petrol was definitely the highest ( Table 4 ). Previous research also demonstrated the time-variable effect of various additives modifying the enzymatic activity of soil contaminated with petroleum derivatives [ 8 , 14 , 15 , 19 , 46 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the η 2 analysis conducted for both coal tar creosote types demonstrated that among all experimental factors, the dose of rhamnolipids had the strongest effect on the determined microbiological and biochemical parameters of soil. Compared with the earlier study on the changes of enzymatic activity of soil contaminated with coal tar creosote subject to stimulation with calcium peroxide [ 43 ] or low-molecular-weight organic acids [ 44 ], the use of rhamnolipids seems to be the most efficient bioremediation treatment option.…”
Section: Discussionmentioning
confidence: 99%